Subchronic Toxicity and Effect of the Methanolic Extract of Micromeria frivaldszkyana (Degen) Velen on Cognition in Male Wistar Rats - Elisaveta Apostolova; Kristina Stavrakeva; Vesela Kokova; Ivica Dimov; Mariya Choneva; Delyan Delev; Ilia Kostadinov; Iliya Bivolarski; Maria Koleva; Tsvetelina Mladenova; Krasimir Todorov; Anelia Bivolarska (Plants, 2025)
Recently, compounds of plant origin have been the focus of increased scientific interest. Micromeria frivaldszkyana is a rare species endemic to Bulgaria, whose biological activity remains unknown. This article aims to evaluate the subchronic toxicity of Micromeria frivaldszkyana methanolic extract and its effect on cognition in rats. Following 90 days of oral administration, a histopathological evaluation of brain, kidney, and liver tissues was conducted. Additionally, serum levels of total bilirubin (TB), conjugated bilirubin (CB), alanine aminotransferase (ALT), aspartate aminotransferase (AST), creatinine (CR), uric acid (UA), and urea (U) were measured. Cognitive function was studied after 7 d of treatment using activity cage test, along with tests for active memory, passive memory, anxiety, spatial and working memory, and explorative activity. The experiments showed no toxic effects of the extract in subchronic application. No adverse effects on brain function were observed after 14 days of treatment. While the extract increased the motor activity of the animals, it did not significantly improve the learning and memory processes. In conclusion, the methanolic extract of Micromeria frivaldszkyana in doses 250 and 500 mg/kg bw did not induce toxicity after 90-day treatment in rats. These doses did not significantly affect central nervous system (CNS) functions, although increased motor activity was observed after 14 days of treatment with the extract.